Sustainable Tourism Development in Boracay Island, Malay, Aklan - Maming, Jimmy Bernabe; Delantar, Alexander Franco F.; Gabuya, Patricio G. (Future Science / FSH-PH Publications, 2021)
Sustainability is regarded as a critical goal in tourism planning and development. Boracay Island has faced challenges and deterioration as a result of rapid growth in tourism without proper planning and management, leading to its six-month temporary closure on May 8, 2018. Through qualitative interviews with key stakeholders, this paper aims to investigate the sustainable tourism development of Boracay Island, Malay, Aklan. Yin's data analysis and procedures were used to create a single case study design. Data was gathered and analyzed using interviews, observations, and data reviews. The study included twenty (20) key informants who were chosen at random. The study's conclusive report yields benefits and costs in three areas: first, economic characteristics of tourism benefit communities and improve the island's economy. However, the island's high cost of living rises, causing inflation. Second, in terms of the environment, its natural resources have been harmed in part by members of the local immigrant and business populations, but they will recover as a result of the recent national and local government efforts to restore the island's ecology. Third, in terms of social structure, improved infrastructure such as good housing and roads create better living conditions for residents. Nonetheless, tourists' influence on the social culture of Boracay Island's young residents is enthralling. The study's output is a theory on sustainable tourism development that will help future research on similar topics and improve the socio-economic quality of life.